Coping and well-being in university students: sex and cultural differences - Rojas-Ruiz, Gloria; Alemany-Arrebola, Inmaculada; Mingorance-Estrada, Ángel C. (Frontiers in Education, 2024)
For the psychological and personal well-being of university students, it is considered essential to study the coping strategies they use when faced with conflictive situations in the academic context and the resources that the institution offers to help them overcome these challenges. The objective of this work is to evaluate the effect of sex and culture on the different coping strategies that higher education students use in the face of the difficulties they face in the academic environment. For this purpose, the questionnaire “Coping Strategies Inventory (CSI)” was applied to a sample of 1,281 university students. The results indicate that there are significant differences in the problem-solving strategies used depending on gender and culture, finding interaction between these variables, with European women being the ones who use active strategies the most. On the contrary, men of Berber origin, are the ones who use less coping strategies, both active (emotional expression and social support) and passive (desiderative thinking), to resolve conflicts.